The Effect Of Counterpressure With A Birthball On Reducing Labor Pain During The First Active Phase - Rohaya, Rohaya; Ana Persari, Devy; Novita, Nesi; Wahyuni, Sari; Jamila, Jamila; Kamalia, Rita (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2024)
Most births are always accompanied by intense pain and sometimes cause trauma to the birth mother. Efforts to relieve pain and provide comfort for mothers giving birth non-pharmacologically include using counterpressure with a birth ball. The research aimed to determine the effect of counterpressure with a birth ball on reducing labor pain during the first active phase. This research design is a pre-experiment with a one-group pretest-posttest design. The total sample was 30 mothers in the first stage of labor. Data collection techniques used a counterpressure questionnaire with a birth ball and a VAS pain scale. Data analysis used paired t-test. The pain scale in the group before treatment averaged 7.94 and after treatment averaged 6.41. The results of data analysis using the paired t-test showed statistically significant results, P Value = 0.000 < 0.05. There is an effect of giving counterpressure with a birth ball on reducing labor pain in the active phase of the first stage. It is hoped that health workers can apply counterpressure with this birth ball as a method of reducing pain.